Class switch towards non-inflammatory, spike-specific IgG4 antibodies after repeated SARS-CoV-2 mRNA vaccination - Irrgang, Pascal; Gerling, Juliane; Kocher, Katharina; Lapuente, Dennis; Steininger, Philipp; Habenicht, Katharina; Wytopil, Monika; Beileke, Stephanie; Schäfer, Simon; Zhong, Jahn; Ssebyatika, George; Krey, Thomas; et al. (Science immunology, 2022)
RNA vaccines are efficient preventive measures to combat the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic. High levels of neutralizing SARS-CoV-2 antibodies are an important component of vaccine-induced immunity. Shortly after the initial two mRNA vaccine doses, the immunoglobulin G (IgG) response mainly consists of the proinflammatory subclasses IgG1 and IgG3. Here, we report that several months after the second vaccination, SARS-CoV-2–specific antibodies were increasingly composed of noninflammatory IgG4, which were further boosted by a third mRNA vaccination and/or SARS-CoV-2 variant breakthrough infections. IgG4 antibodies among all spike-specific IgG antibodies rose, on average, from 0.04% shortly after the second vaccination to 19.27% late after the third vaccination. This induction of IgG4 antibodies was not observed after homologous or heterologous SARS-CoV-2 vaccination with adenoviral vectors. Single-cell sequencing and flow cytometry revealed substantial frequencies of IgG4-switched B cells within the spike-binding memory B cell population [median of 14.4%; interquartile range (IQR) of 6.7 to 18.1%] compared with the overall memory B cell repertoire (median of 1.3%; IQR of 0.9 to 2.2%) after three immunizations. This class switch was associated with a reduced capacity of the spike-specific antibodies to mediate antibody-dependent cellular phagocytosis and complement deposition. Because Fc-mediated effector functions are critical for antiviral immunity, these findings may have consequences for the choice and timing of vaccination regimens using mRNA vaccines, including future booster immunizations against SARS-CoV-2.<br

Clinical and immunological benefits of full primary COVID-19 vaccination in individuals with SARS-CoV-2 breakthrough infections: A prospective cohort study in non-hospitalized adults - Prelog, Martina; Jeske, Samuel D.; Asam, Claudia; Fuchs, Andre; Wieser, Andreas; Gall, Christine; Wytopil, Monika; Müller-Schmucker, Sandra; Beileke, Stephanie; Goekkaya, Mehmet; Kling, Elisabeth; Geldmacher, Christof; et al. (Journal of Clinical Virology, 2024)
Background: SARS-CoV-2 variants of concern (VOC) may result in breakthrough infections (BTIs) in vaccinated individuals. The aim of this study was to investigate the effects of full primary (two-dose) COVID-19 vaccination with wild-type-based SARS-CoV-2 vaccines on symptoms and immunogenicity of SARS-CoV-2 VOC BTIs. Methods: In a longitudinal multicenter controlled cohort study in Bavaria, Germany, COVID-19 vaccinated and unvaccinated non-hospitalized individuals were prospectively enrolled within 14 days of a PCR-confirmed SARS-CoV-2 infection. Individuals were visited weekly up to 4 times, performing a structured record of medical data and viral load assessment. SARS-CoV-2-specific antibody response was characterized by anti-spike-(S)- and anti-nucleocapsid-(N)-antibody concentrations, anti-S-IgG avidity and neutralization capacity. Results: A total of 300 individuals (212 BTIs, 88 non-BTIs) were included with VOC Alpha or Delta SARS-CoV-2 infections. Full primary COVID-19 vaccination provided a significant effectiveness against five symptoms (relative risk reduction): fever (33 %), cough (21 %), dysgeusia (22 %), dizziness (52 %) and nausea/vomiting (48 %). Full primary vaccinated individuals showed significantly higher 50 % inhibitory concentration (IC50) values against the infecting VOC compared to unvaccinated individuals at week 1 (269 vs. 56, respectively), and weeks 5–7 (1,917 vs. 932, respectively) with significantly higher relative anti-S-IgG avidity (78% vs. 27 % at week 4, respectively). Conclusions: Full primary COVID-19 vaccination reduced symptom frequencies in non-hospitalized individuals with BTIs and elicited a more rapid and longer lasting neutralization capacity against the infecting VOC compared to unvaccinated individuals. These results support the recommendation to offer at least full primary vaccination to all adults to reduce disease severity caused by immune escape-variants.
CRIS-Team Scopus Importer:2023-12-29
Keywords: Antibodies; Breakthrough infection; COVID-19 symptoms; SARS-CoV-2; Vaccine effectiveness; Viral load

Comparative Immunogenicity of COVID-19 Vaccines in a Population-Based Cohort Study with SARS-CoV-2-Infected and Uninfected Participants - Peterhoff, David; Einhauser, Sebastian; Beileke, Stephanie; Niller, Hans Helmut; Günther, Felix; Schachtner, Michael; Asbach, Benedikt; Steininger, Philipp; Tenbusch, Matthias; Peter, Antonia Sophia; Gessner, Andre; Burkhardt, Ralph; et al. (Vaccines, 2022)
To assess vaccine immunogenicity in non-infected and previously infected individuals in a real-world scenario, SARS-CoV-2 antibody responses were determined during follow-up 2 (April 2021) of the population-based Tirschenreuth COVID-19 cohort study comprising 3378 inhabitants of the Tirschenreuth county aged 14 years or older. Seronegative participants vaccinated once with Vaxzevria, Comirnaty, or Spikevax had median neutralizing antibody titers ranging from ID50 = 25 to 75. Individuals with two immunizations with Comirnaty or Spikevax had higher median ID50s (of 253 and 554, respectively). Regression analysis indicated that both increased age and increased time since vaccination independently decreased RBD binding and neutralizing antibody levels. Unvaccinated participants with detectable N-antibodies at baseline (June 2020) revealed a median ID50 of 72 at the April 2021 follow-up. Previously infected participants that received one dose of Vaxzevria or Comirnaty had median ID50 to 929 and 2502, respectively. Individuals with a second dose of Comirnaty given in a three-week interval after the first dose did not have higher median antibody levels than individuals with one dose. Prior infection also primed for high systemic IgA levels in response to one dose of Comirnaty that exceeded IgA levels observed after two doses of Comirnaty in previously uninfected participants. Neutralizing antibody levels targeting the spike protein of Beta and Delta variants were diminished compared to the wild type in vaccinated and infected participants.
CRIS-Team Scopus Importer:2022-03-04
Keywords: Comirnaty; Immunogenicity; Neutralizing anti-bodies; Population-based cohort; SARS-CoV-2; Spikevax; Vaccination; Variants of concern VoC; Vaxzevria

Dynamics of humoral and cellular immune responses after homologous and heterologous SARS-CoV-2 vaccination with ChAdOx1 nCoV-19 and BNT162b2 - Vogel, Emanuel; Kocher, Katharina; Priller, Alina; Cheng, Cho Chin; Steininger, Philipp; Liao, Bo Hung; Körber, Nina; Willmann, Annika; Irrgang, Pascal; Held, Jürgen; Moosmann, Carolin; Schmidt, Viviane; et al. (EBioMedicine, 2022)
Background: Vaccines are an important means to overcome the SARS-CoV-2 pandemic. They induce specific antibody and T-cell responses but it remains open how well vaccine-induced immunity is preserved over time following homologous and heterologous immunization regimens. Here, we compared the dynamics of humoral and cellular immune responses up to 180 days after homologous or heterologous vaccination with either ChAdOx1-nCoV-19 (ChAd) or BNT162b2 (BNT) or both. Methods: Various tests were used to determine the humoral and cellular immune response. To quantify the antibody levels, we used the surrogate neutralization (sVNT) assay from YHLO, which we augmented with pseudo- and real virus neutralization tests (pVNT and rVNT). Antibody avidity was measured by a modified ELISA. To determine cellular reactivity, we used an IFN-γ Elispot, IFN-γ/IL Flurospot, and intracellular cytokine staining. Findings: Antibody responses significantly waned after vaccination, irrespective of the regimen. The capacity to neutralize SARS-CoV-2 – including variants of concern such as Delta or Omicron – was superior after heterologous compared to homologous BNT vaccination, both of which resulted in longer-lasting humoral immunity than homologous ChAd immunization. All vaccination regimens induced stable, polyfunctional T-cell responses. Interpretation: These findings demonstrate that heterologous vaccination with ChAd and BNT is a potent alternative to induce humoral and cellular immune protection in comparison to the homologous vaccination regimens. Funding: The study was funded by the German Centre for Infection Research (DZIF), the European Union's “Horizon 2020 Research and Innovation Programme" under grant agreement No. 101037867 (VACCELERATE), the “Bayerisches Staatsministerium für Wissenschaft und Kunst” for the CoVaKo-2021 and the For-COVID projects and the Helmholtz Association via the collaborative research program “CoViPa”. Further support was obtained from the Federal Ministry of Education and Science (BMBF) through the “Netzwerk Universitätsmedizin”, project “B-Fast” and “Cov-Immune”. KS is supported by the German Federal Ministry of Education and Research (BMBF, 01KI2013) and the Else Kröner-Stiftung (2020_EKEA.127).
CRIS-Team Scopus Importer:2022-10-21
Keywords: antibody avidity; BNT162b2; ChAdOx1-nCoV-19; COVID-19; Heterologous vaccination; long-term; maintenance; SARS-CoV-2; T cell immunity; vaccine

Estimates and determinants of sars-cov-2 seroprevalence and infection fatality ratio using latent class analysis: The population-based tirschenreuth study in the hardest-hit german county in spring 2020 - Wagner, Ralf; Peterhoff, David; Beileke, Stephanie; Günther, Felix; Berr, Melanie; Einhauser, Sebastian; Schütz, Anja; Niller, Hans Helmut; Steininger, Philipp; Knöll, Antje; Tenbusch, Matthias; Maier, Clara; et al. (Viruses, 2021)
SARS-CoV-2 infection fatality ratios (IFR) remain controversially discussed with implications for political measures. The German county of Tirschenreuth suffered a severe SARS-CoV-2 outbreak in spring 2020, with particularly high case fatality ratio (CFR). To estimate seroprevalence, underreported infections, and IFR for the Tirschenreuth population aged ≥14 years in June/July 2020, we conducted a population-based study including home visits for the elderly, and analyzed 4203 participants for SARS-CoV-2 antibodies via three antibody tests. Latent class analysis yielded 8.6% standardized county-wide seroprevalence, a factor of underreported infections of 5.0, and 2.5% overall IFR. Seroprevalence was two-fold higher among medical workers and one third among current smokers with similar proportions of registered infections. While seroprevalence did not show an age-trend, the factor of underreported infections was 12.2 in the young versus 1.7 for ≥85-year-old. Age-specific IFRs were <0.5% below 60 years of age, 1.0% for age 60–69, and 13.2% for age 70+. Senior care homes accounted for 45% of COVID-19-related deaths, reflected by an IFR of 7.5% among individuals aged 70+ and an overall IFR of 1.4% when excluding senior care home residents from our computation. Our data underscore senior care home infections as key determinant of IFR additionally to age, insufficient targeted testing in the young, and the need for further investigations on behavioral or molecular causes of the fewer infections among current smokers.
CRIS-Team Scopus Importer:2021-07-02
Keywords: Antibodies; CLIA; ELISA; Infection fatality ratio; Latent class analysis; SARS-CoV-2; Senior care homes; Seroprevalence; Smoking; Underreported infections

Evaluation of surfactant proteins A, B, C, and D in articular cartilage, synovial membrane and synovial fluid of healthy as well as patients with osteoarthritis and rheumatoid arthritis - Hartjen, Nadine; Bräuer, Lars; Reiss, Beate; Claassen, Horst; Beileke, Stephanie; Garreis, Fabian; Hoogeboom, Sebastian; Tsokos, Michael; Etzold, Saskia; Mueller-Hilke, Brigitte; Gelse, Kolja; Mueller, Thomas; et al. (PLoS ONE, 2018)
OBJECTIVE: Surfactant Proteins (SPs) are well known from lung and form, along with phospholipids, a surface-active-layer at the liquid-air-interface of the alveolar lining. They play a major protective role by lowering surface tension, activating innate and adaptive immune defense at the lung mucosal interface, especially during infection. We analyzed the regulation of SPs in human and mouse articular chondrocytes, synoviocytes, and synovial fluid under healthy and inflammatory conditions, as well as in tissues of patients suffering from osteoarthritis and rheumatoid arthritis. METHODS: Immunohistochemistry, RT-PCR, qRT-PCR, ELISA, Western blotting were performed in cell cultures and tissue samples to determine localization, regulation, and concentration of SPs. RESULTS: All four SPs, were expressed by healthy human and mouse articular chondrocytes and synoviocytes and were also present in synovial fluid. Treatment with inflammatory mediators like IL-1β and TNF-α led to short-term upregulation of individual SPs in vitro. In tissues from patients with osteoarthritis and rheumatoid arthritis, protein levels of all four SPs increased significantly compared to the controls used. CONCLUSION: These results show the distribution and amount of SPs in tissues of articular joints. They are produced by chondrocytes and synoviocytes and occur in measurable amounts in synovial fluid. All four SPs seem to be differently regulated under pathologic conditions. Their physiological functions in lowering surface tension and immune defense need further elucidation and make them potential candidates for therapeutic intervention.
EVALuna2:35305

Expression and Localization of Lung Surfactant Proteins in Human Testis - Beileke, Stephanie; Claassen, Horst; Wagner, Walter; Matthies, Cord; Ruf, Christian; Hartmann, Arndt; Garreis, Fabian; Paulsen, Friedrich; Schicht, Martin; Bräuer, Lars (PLoS ONE, 2015)
Surfactant proteins (SPs) have been described in various tissues and fluids including tissues of the nasolacrimal apparatus, airways and digestive tract. Human testis have a glandular function as a part of the reproductive and the endocrine system, but no data are available on SPs in human testis and prostate under healthy and pathologic conditions.The aim of the study was the detection and characterization of the surfactant proteins A, B, C and D (SP-A, SP-B, SP-C, SP-D) in human testis. Additionally tissue samples affected by testicular cancer were investigated.Surfactant proteins A, B, C and D were detected using RT-PCR in healthy testis. By means of Western blot analysis, these SPs were detected at the protein level in normal testis, seminoma and seminal fluid, but not in spermatozoa. Expression of SPs was weaker in seminoma compared to normal testicular tissue. SPs were localized in combination with vimentin immunohistochemically in cells of Sertoli and Leydig.Surfactant proteins seem to be inherent part of the human testis. By means of physicochemical properties the proteins appear to play a role during immunological and rheological process of the testicular tissue. The presence of SP-B and SP-C in cells of Sertoli correlates with their function of fluid secretion and may support transportation of spermatozoa. In seminoma the expression of all SP's was generally weaker compared to normal germ cells. This could lead to a reduction of immunomodulatory and rheology processes in the germ cell tumor.
EVALuna2:4444

Heterologous prime–boost vaccination with ChAdOx1 nCoV-19 and BNT162b2 - Tenbusch, Matthias; Schumacher, Sofie; Vogel, Emanuel; Priller, Alina; Held, Jürgen; Steininger, Philipp; Beileke, Stephanie; Irrgang, Pascal; Brockhoff, Ronja; Salmanton-García, Jon; Tinnefeld, Kathrin; Mijocevic, Hrvoje; et al. (Lancet Infectious Diseases, 2021)
CRIS-Team Scopus Importer:2021-09-10

Higher Infection Risk among Health Care Workers and Lower Risk among Smokers Persistent across SARS-CoV-2 Waves-Longitudinal Results from the Population-Based TiKoCo Seroprevalence Study - Guenther, Felix; Einhauser, Sebastian; Peterhoff, David; Wiegrebe, Simon; Niller, Hans Helmut; Beileke, Stephanie; Steininger, Philipp; Burkhardt, Ralph; Kuechenhoff, Helmut; Gefeller, Olaf; Überla, Klaus; Heid, Iris M.; et al. (International Journal of Environmental Research and Public Health, 2022)
SARS-CoV-2 seroprevalence was reported as substantially increased in medical personnel and decreased in smokers after the first wave in spring 2020, including in our population-based Tirschenreuth Study (TiKoCo). However, it is unclear whether these associations were limited to the early pandemic and whether the decrease in smokers was due to reduced infection or antibody response. We evaluated the association of occupation and smoking with period-specific seropositivity: for the first wave until July 2020 (baseline, BL), the low infection period in summer (follow-up 1, FU1, November 2020), and the second/third wave (FU2, April 2021). We measured binding antibodies directed to SARS-CoV-2 nucleoprotein (N), viral spike protein (S), and neutralizing antibodies at BL, FU1, and FU2. Previous infection, vaccination, smoking, and occupation were assessed by questionnaires. The 4181 participants (3513/3374 at FU1/FU2) included 6.5% medical personnel and 20.4% current smokers. At all three timepoints, new seropositivity was higher in medical personnel with ORs = 1.99 (95%-CI = 1.36-2.93), 1.41 (0.29-6.80), and 3.17 (1.92-5.24) at BL, FU1, and FU2, respectively, and nearly halved among current smokers with ORs = 0.47 (95%-CI = 0.33-0.66), 0.40 (0.09-1.81), and 0.56 (0.33-0.94). Current smokers compared to never-smokers had similar antibody levels after infection or vaccination and reduced odds of a positive SARS-CoV-2 result among tested. Our data suggest that decreased seroprevalence among smokers results from fewer infections rather than reduced antibody response. The persistently higher infection risk of medical staff across infection waves, despite improved means of protection over time, underscores the burden for health care personnel.
CRIS-Team WoS Importer:2023-01-13

Palate Lung Nasal Clone (PLUNC), a Novel Protein of the Tear Film: Three-Dimensional Structure, Immune Activation, and Involvement in Dry Eye Disease (DED) - Schicht, Martin; Rausch, Felix; Beron, Martin; Jacobi, Christina; Garreis, Fabian; Hartjen, Nadine; Beileke, Stephanie; Kruse, Friedrich; Bräuer, Lars; Paulsen, Friedrich (Investigative Ophthalmology & Visual Science, 2015)
Palate Lung Nasal Clone (PLUNC) is a hydrophobic protein belonging to the family of surfactant proteins that is involved in fluid balance regulation of the lung. Moreover, it is known to directly act against gram-negative bacteria. The purpose of this study was to investigate the possible expression and antimicrobial role of PLUNC at the healthy ocular surface and in tears of patients suffering from dry eye disease (DED).Bioinformatics and biochemical and immunologic methods were combined to elucidate the structure and function of PLUNC at the ocular surface. Tissue-specific localization was performed by using immunohistochemistry. The PLUNC levels in tear samples from non-Sjögren's DED patients with moderate dry eye suffering either from hyperevaporation or tear deficiency were analyzed by ELISA and compared with tears from healthy volunteers.Palate Lung Nasal Clone is expressed under healthy conditions at the ocular surface and secreted into the tear film. Protein modeling studies and molecular dynamics simulations performed indicated surface activity of PLUNC. In vitro experiments revealed that proinflammatory cytokines and bacterial supernatants have only a slight effect on the expression of PLUNC in HCE and HCjE cell lines. In tears from DED patients, the PLUNC concentration is significantly increased (7-fold in evaporative dry eye tears and 17-fold in tears from patients with tear deficiency) compared with healthy subjects.The results show that PLUNC is a protein of the tear film and suggest that it plays a role in fluid balance and surface tension regulation at the ocular surface.
EVALuna2:4442

Population-based study of the durability of humoral immunity after SARS-CoV-2 infection - Peterhoff, David; Wiegrebe, Simon; Einhauser, Sebastian; Patt, Arisha J.; Beileke, Stephanie; Günther, Felix; Steininger, Philipp; Niller, Hans H.; Burkhardt, Ralph; Küchenhoff, Helmut; Gefeller, Olaf; Überla, Klaus; et al. (Frontiers in Immunology, 2023)
SARS-CoV-2 antibody quantity and quality are key markers of humoral immunity. However, there is substantial uncertainty about their durability. We investigated levels and temporal change of SARS-CoV-2 antibody quantity and quality. We analyzed sera (8 binding, 4 avidity assays for spike-(S-)protein and nucleocapsid-(N-)protein; neutralization) from 211 seropositive unvaccinated participants, from the population-based longitudinal TiKoCo study, at three time points within one year after infection with the ancestral SARS-CoV-2 virus. We found a significant decline of neutralization titers and binding antibody levels in most assays (linear mixed regression model, p<0.01). S-specific serum avidity increased markedly over time, in contrast to N-specific. Binding antibody levels were higher in older versus younger participants – a difference that disappeared for the asymptomatic-infected. We found stronger antibody decline in men versus women and lower binding and avidity levels in current versus never-smokers. Our comprehensive longitudinal analyses across 13 antibody assays suggest decreased neutralization-based protection and prolonged affinity maturation within one year after infection.
CRIS-Team Scopus Importer:2023-11-03
Keywords: antibody; avidity; COVID-19; durability; longitudinal; neutralization; population-based; SARS-CoV-2

SFTA3 - a novel surfactant protein of the ocular surface and its role in corneal wound healing and tear film surface tension - Schicht, Martin; Garreis, Fabian; Hartjen, Nadine; Beileke, Stephanie; Jacobi, Christina; Sahin, Afsun; Holland, Detlef; Schröder, Henrik; Hammer, Christian; Paulsen, Friedrich; Bräuer, Lars (Scientific Reports, 2018)
The study aimed to characterize the expression and function of SFTA3 at the ocular surface and in tears. Ocular tissues, conjunctival (HCjE) and human corneal (HCE) epithelial cell lines as well as tearfilm of patients suffering from different forms of dry eye disease (DED) were analyzed by means of RT-PCR, western blot, immunohistochemistry, and ELISA. A possible role of recombinant SFTA3 in corneal wound healing was investigated performing in vitro scratch assays. Tear film regulatory properties were analyzed with the spinning drop method and the regulation of SFTA3 transcripts was studied in HCE and HCjE after incubation with proinflammatory cytokines as well as typical ocular pathogens by real-time RT-PCR and ELISA. The results reveal that human ocular tissue as well as tears of healthy volunteers express SFTA3 whereas tears from patients with DED showed significantly increased SFTA3 levels. In vitro wounding of HCE cell cultures that had been treated with recombinant SFTA3 demonstrated a significantly increased wound closure rate and rSFTA3 reduced the surface tension of tear fluid. The results indicate that SFTA3 at the ocular surface seemed to be involved in wound healing and the reduction of surface tension.
EVALuna2:35316

Spectrum bias and individual strengths of SARS-CoV-2 serological tests–A population-based evaluation - Einhauser, Sebastian; Peterhoff, David; Niller, Hans Helmut; Beileke, Stephanie; Günther, Felix; Steininger, Philipp; Burkhardt, Ralph; Heid, Iris M.; Pfahlberg, Annette Bettina; Überla, Klaus; Gefeller, Olaf; Wagner, Ralf (Diagnostics, 2021)
Antibody testing for determining the SARS-CoV-2 serostatus was rapidly introduced in early 2020 and since then has been gaining special emphasis regarding correlates of protection. With limited access to representative samples with known SARS-CoV-2 infection status during the initial period of test development and validation, spectrum bias has to be considered when moving from a “test establishment setting” to population-based settings, in which antibody testing is currently implemented. To provide insights into the presence and magnitude of spectrum bias and to estimate performance measures of antibody testing in a population-based environment, we compared SARS-CoV-2 neutralization to a battery of serological tests and latent class analyses (LCA) in a subgroup (n = 856) of the larger population based TiKoCo-19 cohort (n = 4185). Regarding spectrum bias, we could proof notable differences in test sensitivities and specificities when moving to a population-based setting, with larger effects visible in earlier registered tests. While in the population-based setting the two Roche ELECSYS anti-SARS-CoV-2 tests outperformed every other test and even LCA regarding sensitivity and specificity in dichotomous testing, they didn’t provide satisfying quantitative correlation with neutralization capacity. In contrast, our in-house anti SARS-CoV-2-Spike receptor binding domain (RBD) IgG-ELISA (enzyme-linked-immunosorbant assay) though inferior in dichotomous testing, provided satisfactory quantitative correlation and may thus represent a better correlate of protection. In summary, all tests, led by the two Roche tests, provided sufficient accuracy for dichotomous identification of neutralizing sera, with increasing spectrum bias visible in earlier registered tests, while the majority of tests, except the RBD-ELISA, didn’t provide satisfactory quantitative correlations.
CRIS-Team Scopus Importer:2021-10-29
Keywords: ECLIA; ELISA; Neutralization; SARS-CoV-2; Sensitivity; Serology; Specificity; Spectrum bias; Test accuracy

Time Trend in SARS-CoV-2 Seropositivity, Surveillance Detection- and Infection Fatality Ratio until Spring 2021 in the Tirschenreuth County—Results from a Population-Based Longitudinal Study in Germany - Einhauser, Sebastian; Peterhoff, David; Beileke, Stephanie; Günther, Felix; Niller, Hans Helmut; Steininger, Philipp; Knöll, Antje; Korn, Klaus; Berr, Melanie; Schütz, Anja; Wiegrebe, Simon; Stark, Klaus J.; et al. (Viruses, 2022)
Herein, we provide results from a prospective population-based longitudinal follow-up (FU) SARS-CoV-2 serosurveillance study in Tirschenreuth, the county which was hit hardest in Germany in spring 2020 and early 2021. Of 4203 individuals aged 14 years or older enrolled at baseline (BL, June 2020), 3546 participated at FU1 (November 2020) and 3391 at FU2 (April 2021). Key metrics comprising standardized seroprevalence, surveillance detection ratio (SDR), infection fatality ratio (IFR) and success of the vaccination campaign were derived using the Roche N-and S-Elecsys anti-SARS-CoV-2 test together with a self-administered questionnaire. N-seropositivity at BL was 9.2% (1st wave). While we observed a low new seropositivity between BL and FU1 (0.9%), the combined 2nd and 3rd wave accounted for 6.1% new N-seropositives between FU1 and FU2 (ever seropositives at FU2: 15.4%). The SDR decreased from 5.4 (BL) to 1.1 (FU2) highlighting the success of massively increased testing in the population. The IFR based on a combination of serology and registration data resulted in 3.3% between November 2020 and April 2021 compared to 2.3% until June 2020. Although IFRs were consistently higher at FU2 compared to BL across age-groups, highest among individuals aged 70+ (18.3% versus 10.7%, respectively), observed differences were within statistical uncertainty bounds. While municipalities with senior care homes showed a higher IFR at BL (3.0% with senior care home vs. 0.7% w/o), this effect diminished at FU2 (3.4% vs. 2.9%). In April 2021 (FU2), vaccination rate in the elderly was high (>77.4%, age-group 80+).
CRIS-Team Scopus Importer:2022-06-17
Keywords: case fatality ratio; elderly; infection fatality ratio; longitudinal; population-based; SARS-CoV-2; senior care homes; seroprevalence; surveillance detection ratio; vaccination